Curcumin Release from Biomaterials for Enhanced Tissue Regeneration Following Injury or Disease - Adelle E. Hamilton; Ryan J. Gilbert (Bioengineering, 2023)
Curcumin, a bioactive phenol derived from turmeric, is an antioxidant, anti-inflammatory, and antibacterial molecule. Although curcumin exhibits beneficial effects in its innate form, it is highly hydrophobic, which leads to poor water solubility and, consequently, low bioavailability. The lack of bioavailability limits curcumin’s effectiveness as a treatment and restricts its use in clinical applications. Furthermore, to achieve beneficial, clinically relevant results, high doses of curcumin are required for systemic administration. Many researchers have utilized biomaterial carriers, including electrospun fibers, nanoparticles, hydrogels, and composite scaffolds, to overcome curcumin’s principle therapeutic limitation of low bioavailability. By using biomaterials to deliver curcumin directly to injury sites, researchers have harnessed the beneficial natural properties of curcumin while providing scaffolding to support tissue regeneration. This review will provide an in-depth overview of the literature that utilizes biomaterial delivery of curcumin for tissue regeneration in injury and disease models.